Exploring Sustainable Gayo Coffee Pricing and Branding Strategies in the Marketplace Ecosystem - Sulistio Ningsih; Karimi; Mena Sari; Desi Purnamasari; Feby Ayu Diwa; Mubarik Iwarianta (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to explore sustainable Gayo coffee pricing and branding strategies in the digital marketplace ecosystem, and analyze how these strategies influence consumer perceptions of value, trust, and purchase intention. This study starts from the hypothesis that integrating sustainability values ​​into pricing and branding strategies can increase the competitiveness of Gayo coffee in the digital market. The study used a qualitative approach with an exploratory case study design. The research subjects included Gayo coffee MSMEs that actively market their products through national marketplaces in the Central Aceh region. Data were collected through in-depth interviews with business owners, observations of digital marketplace storefronts, and analysis of branding content and pricing information. Data analysis was conducted using thematic analysis to identify patterns of pricing strategies, branding narratives, and sustainability practices communicated to consumers. The results show that Gayo coffee pricing strategies tend to use a value-based pricing approach linked to product quality, certification, and sustainability stories. Meanwhile, branding focuses on narratives of origin, local wisdom, and environmentally friendly practices. However, the integration of sustainable pricing and branding strategies has not been carried out consistently and optimally across all MSMEs. The findings of this study provide practical implications for Gayo coffee MSMEs in designing more integrated and sustainability-oriented pricing and branding strategies in digital marketplaces. Policy-wise, the results can serve as a reference for stakeholders in developing a sustainable coffee marketing ecosystem. Further research is recommended to develop a quantitative model and test the impact of this strategy on sales performance and consumer loyalty.